MANAJEMEN KURIKULUM CAMBRIDGE PADA PROGRAM KELAS INTERNASIONAL DI CHALIDANA ISLAMIC SCHOOL PRIMARY GRESIK - Janah, Eliya Uslifatul; Widiyanah, Ima (STKIP Pesisir Selatan, 2026)
Systematically designed curriculum management can improve the quality of the learning process and support the achievement of educational goals more effectively. Furthermore, successful curriculum implementation is also influenced by good coordination between the principal, teachers, and stakeholders in the education system. This study aims to examine the implementation of the Cambridge Curriculum in the international program at Chalidana Islamic School Primary Gresik, covering planning, organization, implementation, and evaluation. This study employs a qualitative approach with a descriptive design. Data collection was conducted through in-depth interviews, observations, and document analysis involving the school principal, the Cambridge program coordinator, Cambridge subject teachers, homeroom teachers, and students. The collected data were then analyzed using the approach proposed by Miles et al. (2014), which includes data condensation, data presentation, and the drawing and verification of conclusions. The results of the study indicate that the application of the POAC management functions (Planning, Organization, Actuating, Controlling) supports the management of the Cambridge Curriculum in international class programs at the elementary school level.